CFD simulation and flow-induced vibration evaluation of PWR steam generator U tubes. (November 2021) - Guangming, Xiong; Yipeng, Wang; Teng, Long; Kai, Guo; Wei, Tan
Abstract: For new types of steam generators (SG) for pressurized water reactors (PWRs), the flow-induced vibration (FIV) of U tubes is one of the most important potential failure modes. The presence of numerous U tubes complicates the FIV process and makes it difficult to model. Although a global media model with a coarse mesh has been used to simplify the flow field of SG tube bundles, precise outputs cannot be obtained to evaluate the FIV, so a more accurate model needs to be developed. Support failure, support clearance, and offset are the key factors and are believed to significantly affect the FIV, but it is unclear how to properly account for this factor and its quantitative influence. In this work, a more accurate CFD simulation of two-phase flow and heat transfer on the SG secondary side is conducted by combining the local solid model with the global porous media model. In addition, comprehensive finite element model (FEM) models are built to study the quantitative influence of sensitive factors on FIV. The results show that the newly designed SG satisfied the FIV requirements. The maximum flow-elastic instability (FEI) coefficient increases as the support failure increases. The turbulence buffeting stress amplitude is lower than the fatigue stress limit. The most significant fretting wear occurs when the support clearance is near 2 times the nominal clearance, and the U tube offsets are beneficial to reducing the fretting wear.